Kristen Borkovec: capstone - Borkovec, Kristen, artist (Colorado State University. Libraries, 2017)
The artist's statement: As a painter, I primarily focus on abstract work and the detail in eyes. Most of my work consists of the use of palette knives, unique brush textures, pouring paint, and dripping techniques. I love experimenting with different color palettes and color mixtures. I have been known for combining colors that normally wouldn't go together but I manage to make them work extremely well together. The way the paint swirls and blends together inspires me to do more. I wasn't always interested in abstract art. Before that I attempted to paint figures and fantasy scenes but I never felt like that was what I was meant to paint. After a long summer of deciding what I wanted to do I came across some abstract artists that inspired me to reinvent my artistic image. My work is an endless search for trying to interpret my thoughts and ideas through abstract art. I use my art to express my emotional persona and share my passion I feel for my work to others who take interest. My personal feelings and passions are my primary focus in my art. I want my paintings to express emotion and allow for my audience to develop their own emotional interpretation based on my art. My use of color is vitally important to the intricacy of my paintings. Color conveys the emotion I was feeling during the creation of each painting and builds upon my unique use of texture. My investigation of color palette has broadened my range of color and ideas for my paintings, which has included me pulling color palettes from other artists and from vibrant photos. My art also explores the idea of synesthesia where one interprets music through paintings. Although I do not have synesthesia I am trying to channel that part of my brain which creates colors from music. This study has been very difficult but I have managed to create intense color palettes from listening to music. Through my research, I continue to experiment with unique color palettes, textures, and expression to further develop my abstract creativity.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting